Crosstalk between lactate and tumor-associated immune cells: clinical relevance and insight - Sun, Kemin; Shen, Ye; Xiao, Xiang; Xu, Hao; Zhang, Quanli; Li, Ming (Frontiers in Oncology, 2024)
Lactate, which was traditionally viewed as a metabolic byproduct of anaerobic glycolysis, has emerged as a significant signaling molecule involved in the development of tumors. Current studies highlight its dual function, where it not only fuels tumor development but also modulates immune responses. Lactate has an effect on various tumor-associated immune cells, promoting immunosuppressive conditions that facilitate tumor growth and immune evasion. This phenomenon is strongly associated with the Warburg effect, a metabolic shift observed in many cancers that favors glycolysis over oxidative phosphorylation, resulting in elevated lactate production. Exploring the complex interplay between lactate metabolism and tumor immunity provides a novel understanding regarding the mechanisms of tumor immune evasion and resistance to therapies. This review discusses the unique biology of lactate in the TME, its impact on immune cell dynamics, and its potential as a tumor treatment target.